2002
DOI: 10.1029/2001jd001092
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic model of the northern annular mode

Abstract: [1] The northern annular mode (NAM) is the leading mode of variability in the Northern Hemisphere. The NAM consists of a meridional dipole of the zonal mean zonal wind that extends into the stratosphere during the winter season. During the high-index state of the NAM, high-latitude westerly winds are stronger than normal, leading to a stronger and colder polar vortex. Over the past few decades, observations show a trend toward higher NAM index values. To investigate whether this trend is a result of natural va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…(1) aerosol heating of the sunlit portion of the lower stratosphere enhances the meridional temperature gradient, (2) this strengthens the westerly zonal winds near the tropopause, (3) planetary waves propagating upwards in the troposphere are refracted away from the pole due to the altered wind shears, further allowing the westerlies to strengthen, (4) the enhanced westerlies propagate down to the surface via wavemean flow interaction reinforced by a positive feedback between the zonal wind anomalies and tropospheric eddies, (5) strengthened westerly flow near the ground creates the surface temperature response pattern typical of the AO. This mechanism is consistent with the behavior of GCMs [Shindell et al, 2001;Stenchikov et al, 2002], mechanistic models [Eichelberger and Holton, 2002;Polvani and Kushner, 2002], and observations [Kodera, 1994;Perlwitz and Graf, 1995;Robinson, 2000;Lorenz and Hartmann, 2003;Perlwitz and Harnik, 2003]. This mechanism is also consistent with the observation of a strong dynamical response only during the NH cold-season, when dynamical connections between the troposphere and stratosphere are strongest.…”
Section: D05104supporting
confidence: 88%
“…(1) aerosol heating of the sunlit portion of the lower stratosphere enhances the meridional temperature gradient, (2) this strengthens the westerly zonal winds near the tropopause, (3) planetary waves propagating upwards in the troposphere are refracted away from the pole due to the altered wind shears, further allowing the westerlies to strengthen, (4) the enhanced westerlies propagate down to the surface via wavemean flow interaction reinforced by a positive feedback between the zonal wind anomalies and tropospheric eddies, (5) strengthened westerly flow near the ground creates the surface temperature response pattern typical of the AO. This mechanism is consistent with the behavior of GCMs [Shindell et al, 2001;Stenchikov et al, 2002], mechanistic models [Eichelberger and Holton, 2002;Polvani and Kushner, 2002], and observations [Kodera, 1994;Perlwitz and Graf, 1995;Robinson, 2000;Lorenz and Hartmann, 2003;Perlwitz and Harnik, 2003]. This mechanism is also consistent with the observation of a strong dynamical response only during the NH cold-season, when dynamical connections between the troposphere and stratosphere are strongest.…”
Section: D05104supporting
confidence: 88%
“…This mechanism includes changes in the upward and meridional wave fluxes that are caused either by variations of the refractive properties of the lower stratospheric flow (e.g., Hartmann et al 2000) or by downward reflection from higher stratospheric levels (Perlwitz and Harnik 2004). Other mechanisms include a downward progression of zonal mean anomalies via eddy-mean flow interaction (e.g., Eichelberger and Holton 2002). Song and Robinson (2004) suggested that when the downward-progressing zonal mean zonal circulation anomalies reach the tropopause, the response to stratospheric anomalies is amplified by eddy (i.e., wave) feedbacks.…”
Section: Introductionmentioning
confidence: 98%
“…In simulations with increased CO 2 , Shindell et al [1999] found an increase in the surface AO in a middle atmosphere GCM (with a good representation of the stratosphere) but not in a tropospheric GCM (with only two levels in the stratosphere). They suggested that planetary wave refraction away from the stratosphere results in a stronger polar vortex which modifies the circulation at the surface (see also the mechanistic model of Eichelberger and Holton [2002]). In contrast Gillett et al [2002] found in a middle atmosphere GCM with doubled CO 2 that the polar vortex weakened due to enhanced tropospheric wave driving.…”
Section: Introductionmentioning
confidence: 99%